Validity and Legal Consequences of Oral Agreements in Business Disputes: Reconstruction of Proof Based on Substantive Justice (A Case Study on a Construction Contract Decision) - Ismayani (Inovasi Pratama Internasional. Ltd, 2027)
Oral agreements remain widely used in Indonesian construction business, yet their validity and enforceability often spark dispute due to the challenges of proof. This study examines the legal validity and consequences of oral charter-party contracts (pemborongan) through the lens of substantive justice, taking the Supreme Court Decision No. 2345 K/Pdt/2021 as a case study. Employing a normative juridical method with a qualitative case approach, the research analyzes how Indonesian civil law, particularly Articles 1320, 1338, and 1601b of the Civil Code, permits oral contracts in construction works, while procedural law under HIR and the ITE Law imposes a high evidentiary burden. The findings reveal that formalistic approaches by lower courts often nullify oral agreements merely due to lack of documentary proof. In contrast, the Supreme Court reconstructed the parties’ consensus by integrating partial payment evidence, electronic communications, and witness testimonies, grounding its reasoning on substantive justice (keadilan substantif). The decision produced legal consequences including the obligation to pay outstanding contract price, compensation, and legal costs. The study proposes an evidentiary reconstruction model that shifts the paradigm from written-document supremacy to a multi-faceted, contextual proof assessment. This model reinforces the principle of good faith and offers a doctrinal framework for judges to resolve similar business disputes without sacrificing legal certainty. The conclusion underlines the urgency of harmonizing formal procedural rules with the substantive truth-seeking function of the judiciary.